Effect of Barangay Bagsakan system to farmers' profitability the case of small-scale farmers in Davao City - Salvana, Meryll G.
For many years, farmers have depended on traders and middlemen in marketing their produce. However, with the emergence of consolidation centers such as Gulayan sa Barangay, Farmers' Market and Barangay Bagsakan, farmers were given new options as to where they can sell their produce. Barangay Bagsakan Centers allow farmers to sell their products without going through different intermediaries. The role played by this system might be beneficial to small-scale farmers. This study aimed to determine the effect of Barangay Bagsakan System to vegetable farmers' profitability in Davao City using Propensity Score Matching. Moreover, other factors as Barangay Bagsakan attributes were included to determine what affects farmers' decision to supply to these kinds of outlets. Results showed that farmers were encouraged to sell their produce to Barangay Bagsakan due to convenience of its location. Futhermore, farmers who supply to Barangay Bagsakan tend to get lower income compared to those who supply to other market channels. However, this only applies since Barangay Bagsakan has little or low capacity to purchase farmers' vegetables. It was recommended that the government should provide cash loans to Barangay Bagsakan so the latter would be able to buy larger volume of vegetables.